Bevacizumab radiosensitizes non-small cell lung cancer xenografts by inhibiting DNA double-strand break repair in endothelial cells. Issue 1 (28th August 2015) - Gao, Hui; Xue, Jianxin; Zhou, Lin; Lan, Jie; He, Jiazhuo; Na, Feifei; Yang, Lifei; Deng, Lei; Lu, You
Highlights: Biweekly bevacizumab induces periodical vascular normalization in NSCLC xenograft model. Radiosensitization induced by bevacizumab is not dependent on vascular normalization. Bevacizumab inhibits DSBs' repair of ECs post irradiation, and promotes their apoptosis. Bevacizumab inhibits the activation of PI3K/Akt/DNA-PKcs signaling pathway post irradiation. Abstract: The aims of this study were to evaluate the effects of biweekly bevacizumab administration on a tumor microenvironment and to investigate the mechanisms of radiosensitization that were induced by it. Briefly, bevacizumab was administered intravenously to Balb/c nude mice bearing non-small cell lung cancer (NSCLC) H1975 xenografts; in addition, bevacizumab was added to NSCLC or endothelial cells (ECs) in vitro, followed by irradiation (IR). The anti-tumor efficacy, anti-angiogenic efficacy and repair of DNA double-strand breaks (DSBs) were evaluated. The activation of signaling pathways was determined using immunoprecipitation (IP) and WB analyses. Finally, biweekly bevacizumab administration inhibited the growth of H1975 xenografts and induced vascular normalization periodically. Bevacizumab more significantly increased cellular DSB and EC apoptosis when administered 1 h prior to 12 Gy/1f IR than when administered 5 days prior to IR, thereby inhibiting tumor angiogenesis and growth. In vitro, bevacizumab more effectively increased DSBs and apoptosis prior to IR and inhibited the clonogenic survival of ECs but not NSCLC cells. Using IP and WB analyses, we confirmed that bevacizumab can directly inhibit the phosphorylation of components of the VEGR2/PI3K/Akt/DNA-PKcs signaling pathway that are induced by IR in ECs. In conclusion, bevacizumab radiosensitizes NSCLC xenografts mainly by inhibiting DSB repair in ECs rather than by inducing vascular normalization.